2002
DOI: 10.1021/jf0203500
|View full text |Cite
|
Sign up to set email alerts
|

Squalene Content and Antioxidant Activity of Terminalia catappa Leaves and Seeds

Abstract: Squalene was identified by gas chromatography-mass spectrometry and high-performance liquid chromatography (HPLC) spiking analyses in the supercritical CO(2) extracts of freeze-dried abscisic leaves of Terminalia catappa L. When the freeze-dried abscisic, senescent, mature, and immature leaves and seeds were subjected to supercritical CO(2) extraction at 40 degrees C and 3000 psi and HPLC quantitation, squalene contents were 12.29, 2.42, 1.75, 0.9, and 0% in the extracts and corresponding to 1499, 451, 210, 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 10 publications
3
60
0
3
Order By: Relevance
“…The kernels of Terminalia catappa are good sources of proteins rich in essential amino acids (22-25%), lipids (35-52%), unsaturated fatty (oleic acid and linoleic acid), and minerals among which the most important are potassium (9280±0.14 mg/100 g), calcium (827.20±2.18 mg/100 g) and magnesium (798.6±0.32 mg/100 g) (Oduro et al, 2009;Matos et al, 2009;Ezeokonkwo & Dodson, 2004;Nwosu, Dosumu, & Okocha, 2008). Studies on the nutritional value and biological activity of the kernel of Terminalia catappa revealed that it has a good digestibility, exerts a strong antioxidant activity, possesses anti-HIV properties, anti-asthma properties, anti-inflammatory, anti-carcinogenic, antibacterial and hepatoprotective properties (AOAC, 1975;Dorsch & Wagner, 1991;Ko, Weng, & Chiou, 2002;Ko, Weng, Lin, & Chiou, 2003;Lin, Hsu, & Lin, 1999;Nagappa, Thakurdesai, Venkat, & Singh, 2003;Teotia & Singh, 1997;Atnasooriya & Dharmasiri, 2000). In view of all this potential, it is critically important to promote processing and consumption of this tropical fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The kernels of Terminalia catappa are good sources of proteins rich in essential amino acids (22-25%), lipids (35-52%), unsaturated fatty (oleic acid and linoleic acid), and minerals among which the most important are potassium (9280±0.14 mg/100 g), calcium (827.20±2.18 mg/100 g) and magnesium (798.6±0.32 mg/100 g) (Oduro et al, 2009;Matos et al, 2009;Ezeokonkwo & Dodson, 2004;Nwosu, Dosumu, & Okocha, 2008). Studies on the nutritional value and biological activity of the kernel of Terminalia catappa revealed that it has a good digestibility, exerts a strong antioxidant activity, possesses anti-HIV properties, anti-asthma properties, anti-inflammatory, anti-carcinogenic, antibacterial and hepatoprotective properties (AOAC, 1975;Dorsch & Wagner, 1991;Ko, Weng, & Chiou, 2002;Ko, Weng, Lin, & Chiou, 2003;Lin, Hsu, & Lin, 1999;Nagappa, Thakurdesai, Venkat, & Singh, 2003;Teotia & Singh, 1997;Atnasooriya & Dharmasiri, 2000). In view of all this potential, it is critically important to promote processing and consumption of this tropical fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of incubation times on oil extraction yield at 50℃ (Ko, et al, 2002). Consequently, the presence of a high content of squalene in Camellia oleifera seed oil would improve its nutraceutical value (Xu, et al, 2011).…”
Section: Regulation) (2003)mentioning
confidence: 99%
“…Relatively high levels of eicosanol (15.45%), squalene (12.51%), tocoferol derivatives (9.78%) and linoleic acid (8.52%) were detected in the samples, indicating that the coextraction of non-polyphenolic components may be affecting the antioxidant activities of the extracts. Several studies have attributed many functional properties to those compounds, which are mainly associated with their high antioxidant activity (Baldioli, Servili, Perretti, & Montedoro, 1996;Ko, Weng, & Chiou, 2002).…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Squalene is a triterpenic hydrocarbon, a known natural antioxidant commonly used in folk medicine to treat chronic diseases due to its antitumor and anticarcinoma activities (Ko et al, 2002). Because its main sources, shark liver and olive oils, have been extensively studied and explored, others squalene sources should be investigated.…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%